In vitro and in vivo effects of reovirus on HPV16-transformed mice cells - Figova, K; Sobotkova, E; Duskova, M; Ludvikova, V; Vonka, V; Eckschlager, T (Neoplasma, 2010)
Oncolytic viruses are examined to serve as anticancer therapeutics. It is expected that in addition to direct oncolytic effect their action will also help eliciting a solid antitumor immunity. In presented series of experiments we have employed two HPV16-transformed mouse (strain C57/B6) cell lines, TC-1 and MK16/III/ABC (MK16), and reovirus type 3, strain Dearing (RV). Both cell lines are highly susceptible to RV and produce large amounts of infectious virus in vitro while normal human are not susceptible to RV. Still, some differences were encountered. TC-1 cells produced moderately lesser amounts of infectious virus, but, paradoxically, were more efficient producers of delta1 antigen of RV and as a consequence of virus infection died more rapidly than simultaneously infected MK16 cells. Minor differences between the cell lines were observed in the percentage of cells arrested in theG2/M phase of the cell cycle and in some markers of apoptosis. When inoculating high doses (5x106) of infected cells (MOI 10 PFU/cell) into syngeneic animals their oncogenic activity was strongly suppressed, nearly completely in the case of MK16 cells and somewhat less efficiently in the case of more oncogenic TC-1 cells. Immunizing experiments in which non-oncogenic doses (106) of RV infected TC-1 cells were tested in parallel with the same doses of irradiated cells brought surprising results. When immunized animals were challenged with TC-1 cells, the irradiated cells proved to be a much better immunogen that the infected cells. However, when challenged with MK16 cells the opposite was true. It is believed that this difference was associated with the different biological properties of the cell lines tested. Keywords: reovirus type 3, HPV16-transformed mouse cell lines, apoptosis, cell cycle, immunization/challenge experiments.
Keywords: Animals; Female; buněčné linie; lidský papilomavirus 16; onkolytická viroterapie; ženské pohlaví; geny ras; Cancer Vaccines; Mice; Oncolytic Virotherapy; Genes, ras; myši; imunizace; Cell Line; Immunization; protinádorové vakcíny; Cell Transformation, Neoplastic; Reoviridae; nádorová transformace buněk; Human papillomavirus 16; zvířata; Mice, Inbred C57BL; myši inbrední C57BL